MENUMBUHKAN SIKAP POSITIF MASYARAKAT TERHADAP BAHASA INDONESIA SEBAGAI WUJUD NASIONALISME - Erwanto, Erwanto (LPPM STKIP PGRI Bandar Lampung, 2018)
Bahasa Indonesia not only as a communication tool to deliver the process of public relations Indonesia, but it could be able to change the whole order of community life, creating an atmosphere of intimacy and togetherness in the community that ultimately a sense of kinship in society. Indonesian is good and right way is the Indonesian language that it suitable fits with the determinants of true communication in the application of rules of language. The understanding of the people about the usage of good and correct Indonesian language can pride and loyalty to the Indonesian language that is able to grow a positive attitude toward the Indonesian language. This positive attitude encourages the people to maintain, develop and use the Indonesian language as a symbol of identity and community unity.